Production and Characterization of MWCNTs Produced by Non- Stationary Current Regimes in Molten LiCl - Aleksandar T. Dimitrov, Abdulaqim Ademi, Anita Grozdanov, Perica Paunovic (Trans Tech Publications, Switzerland, 2013)
This article presents production and characterizations of MWCNTs produced by non-stationary current regimes into lithium molten chloride. In order to improve the process of MWCNTs production, instead of applying a constant cathode potential, the method of reversing the potential was applied. It should be mentioned that during the process of electrolysis reduced lithium intercalate at graphite surface and generates a high mechanical stress that causes exfoliation of the graphite cathode. This phenomenon enables electrochemical synthesis of MWCNTs to be possible. The measurements were performed in temperature interval from 700 to 800°C. Several techniques were employed for characterization, i.e. electron microscopy (SEM and TEM), Raman spectroscopy, thermo gravimetric and differential thermal analysis (TGA and DTA). SEM and TEM images show that nanotubes are mostly of curved shape with length of 1÷20 μm and diameter of 20÷40 nm. Raman peaks indicate that the crystal lenity of produced nanotubes is rather low. The obtained results suggest that formed product contains of up to 80% MWCNTs, the rest being non-reacted graphite and fullerenes. DTA curves show that combustion process of the nanotubes takes place in two stages, i.e. at 450°C and 720°C. At the lower temperature combustion of MWCNTs occurs, while at higher one fullerenes and non-reacted graphite particles burn.